Collegial effect of carbonaceous hybrid fillers in mixed matrix membrane development - Murugiah, P.S. (2019)
One of the major limitations in mixed matrix membrane (MMM) development is difficulty in achieving homogenous filler dispersion in polymer continuous phase. In the past, fillers are often functionalized to improve their dispersion properties in polymer matrix. However, this method is laborious and could deteriorate the intrinsic properties of the native filler particles. Instead of functionalizing the filler, a technique of integrating hybrid fillers for dispersion enhancement is attempted in this work. Accordingly, two different carbonaceous nanofillers, namely carbon nanofiber (CNF) and graphene oxide (GO) were synergistically incorporated into glassy polymer to synthesize a novel MMM for CO2/CH4 separation. The collegial effect of combining two nanofillers was found to render homogenous filler dispersion quality especially at 2 wt CNF/3 wt GO (2C/3G) and 3 wt CNF/2 wt GO (3C/2G) filler loadings. The CNF particles dispersed between GO nanosheets and inhibited the restacking of GO, whilst the strong steric effect imposed by GO nanosheets improved the dispersion of CNF particles in the polymer matrix. Upon the addition of hybrid fillers, thermal and mechanical properties of MMMs were enhanced. The optimum gas separation performance was found at 2C/3G filler loading with CO2/CH4 selectivity of 59.70 and CO2 permeability of 62.32 Barrer. This revealed a notable enhancement of 712 and 23 in CO2/CH4 selectivity and CO2 permeability, respectively. Â© 2018 Elsevier B.V.